Faktor-Faktor Yang Mempengaruhi Perkembangan Market Share Bank Syariah: Study Kasus Bank Bukopin Syariah Periode 2018-2022 - Oktaria Marlinda; Habriyanto Habriyanto; Muhammad Subhan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to examine the Factors That Influence The Development Of Market Share At Bank Bukopin Syariah For The 2018-2022 Period. The method in this research is quantitative. The data used in this research is time series data for the period 2018 to 2022. The results of this research show that there is a positive and significant influence of Return on Assets (ROA) on Market Share at Bank Bukopin Syariah. There is a positive and significant influence of the Capital Adequancy Ratio (CAR) on the Market Share at Bank Bukopin Syariah. There is a positive and significant influence of Financing To Ratio (FDR) on Market Share at Bank Bukopin Syariah. There is a positive and significant influence simultaneously between Return On Assets (ROA), Capital Adequancy Ratio (CAR) and Financing To Ratio (FDR), on the Market Share at Bank Bukopin Syariah. Based on the research results, it is best to use a sample of companies operating in industries other than manufacturing and increase the research period so that the sample size is larger so that the research results can be compared and not only limited to the manufacturing industry.